Truth vs. justification: Contrasting heterodox and mainstream thinking on development via the example of austerity in Africa - Alice Sindzingre (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
The differences between mainstream and 'heterodox' theories and policies have become increasingly blurred, and this dynamic has also affected heterodox analyses of development. Being trapped by the primacy of the statistics-based methodological imperative, much heterodox thinking on development does not distinguish itself from the mainstream and its abandonment of reflection on the theoretical causalities that underlie policies. In this context, a conceptual framework is elaborated that focuses on the relationships between theory and policy, which allows for the argument that differences exist between heterodox and mainstream stances. Indeed, there is no direct translation between theory and policy. The criterion of validity of theory is truth. In contrast, a policymaker's domain is action, and the criterion of validity is the efficiency of the policy given its goals, as well as that of justification. The fact that a policymaker is indifferent to the truth (or falsehood) of a theoretical assumption is shown via the example of the austerity reform programmes of international financial institutions implemented in SubSaharan Africa. The 2020 pandemic is a 'natural experiment' showing that governments and international agencies can discard overnight the theories that have previously demonstrated the truth of the causalities underlying austerity policies and devise huge financial support, hence simultaneously showing that policymakers do not believe that these theories are true. If rich economies are threatened by a massive shock, policies manifest their disconnection from theories that have been previously imposed as 'true', notably upon developing economies, this 'truth' being the justification for conditional lending and an element of policy efficiency. This example delineates the specificity of heterodox reflections on development. Attitudes vis-à-vis truth and the relationships between theory and policy are in fact ethical attitudes: deontological attitudes (as opposed to utilitarianism) characterise heterodox stances, i.e., the consequences of policies are evaluated in terms of norms.
Keywords: A13; B40; B50; O10; 330; economic development; heterodox economy theory; truth; economic policy; austerity